Boosting Employee Engagement in Times of Changing Working Conditions: An Empirical Study Based on A Self-Determination Theory Perspective - Siahaan, Ricky Daniel; Musadieq, Mochammad Al; Nurtjahjono, Gunawan Eko (The International Journal of Accounting and Business Society, 2024)
Purpose — This study aims to predict the factors that may boost and even generate voluntary employee engagement in the midst of changing working conditions to improve employee well-being and performance from a self-determination theory perspective. Design/methodology/approach — This study employs partial least squares structural equation modeling as a data analysis method. By judgmental sampling, the study model was analyzed using 150 surveys from cashiers in one of the regional offices of one of the SOEs in the financial services industry in Indonesia. Findings — This empirical study yielded two fundamental findings. First, autotelic personality, authentic leadership, and perceived organizational support significantly affect employee engagement and, in turn, significantly affect employee well-being and employee performance. Second, the results of this study contribute in several aspects, both theoretically and practically, particularly by offering a better understanding of the dynamic process of employee engagement. Theoretically, employee engagement is a form of individually controlled motivated behavior. Practically, to generate voluntary employee engagement, every employee needs to fulfill the three basic psychological needs of competence, autonomy, and relatedness - where the test results suggest that autotelic personality, authentic leadership, and perceived organizational support, respectively, may satisfy these three basic psychological needs. Practical implications — Empirical study findings suggest that perceived organizational support needs to be encouraged, specifically in implementing good human resources practices, if companies are committed to improving employee engagement in times of changing working conditions. Originality/value — This study provides an empirical-based framework that explains how the satisfaction of the three basic psychological needs of competence, autonomy, and relatedness may lead to voluntary employee engagement and, in turn, simultaneously promote employee well-being and employee performance. Keywords — Autotelic Personality, Authentic Leadership, Perceived Organizational Support, Employee Engagement, Employee Well-Being, Employee Performance, Self-Determination Theory. Paper type — Case study